2019
DOI: 10.1016/j.jhep.2019.06.032
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus-induced modulation of liver macrophage function promotes hepatocyte infection

Abstract: Background and aims. Liver macrophages can be both involved in pathogen clearance and/or pathogenesis. To get further insight on their role during chronic hepatitis B virus (HBV) infections, our aim was to phenotypically and functionally characterize in vivo and ex vivo the interplay between HBV, primary human liver macrophages (PLM) and primary blood monocytes differentiated into pro-inflammatory or anti-inflammatory macrophages (M1-MDM or M2-MDM, respectively).Results. We evidenced the presence of HBc protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 71 publications
3
72
0
Order By: Relevance
“…In agreement with this hypothesis, Faure-Dupuy et al demonstrated that exposure to HBV attenuated cytokine release by pro-inflammatory hepatic macrophages and enhanced cytokine production by anti-inflammatory hepatic macrophages (65). This modulation suppresses the antiviral surveillance and favors the establishment of an infection (65). Taken together, a high HBV/HCV titer not only inhibits pro-inflammatory macrophage polarization but also promotes macrophages differentiating toward a tolerogenic phenotype, which favors HBV/HCV development by releasing immunoregulation cytokine IL-10.…”
Section: The Role Of Hepatic Macrophages In Viral Hepatitismentioning
confidence: 67%
See 2 more Smart Citations
“…In agreement with this hypothesis, Faure-Dupuy et al demonstrated that exposure to HBV attenuated cytokine release by pro-inflammatory hepatic macrophages and enhanced cytokine production by anti-inflammatory hepatic macrophages (65). This modulation suppresses the antiviral surveillance and favors the establishment of an infection (65). Taken together, a high HBV/HCV titer not only inhibits pro-inflammatory macrophage polarization but also promotes macrophages differentiating toward a tolerogenic phenotype, which favors HBV/HCV development by releasing immunoregulation cytokine IL-10.…”
Section: The Role Of Hepatic Macrophages In Viral Hepatitismentioning
confidence: 67%
“…It is likely that a high virus titer suppresses the antiviral activity of hepatic macrophages and polarizes hepatic macrophages toward a tolerogenic phenotype. In agreement with this hypothesis, Faure-Dupuy et al demonstrated that exposure to HBV attenuated cytokine release by pro-inflammatory hepatic macrophages and enhanced cytokine production by anti-inflammatory hepatic macrophages (65). This modulation suppresses the antiviral surveillance and favors the establishment of an infection (65).…”
Section: The Role Of Hepatic Macrophages In Viral Hepatitismentioning
confidence: 82%
See 1 more Smart Citation
“…The level of anti‐inflammatory macrophages maker, IL‐10, was higher when exposed to HBV while pro‐inflammatory cytokines (IL‐6 and IL‐1β) were downregulated. This phenotype was similar in monocytes‐derived macrophages . Li et al suggested that HBsAg enabled monocytes to highly express cell surface inhibitors (PD‐L1 and HLA‐E) and anti‐inflammatory factors (TNF‐α, TGF‐β and IL‐10) to interact with NK cells, which led to regulatory NK cells differentiation, further inhibited T‐cell activation.…”
Section: Relationship Between Host and Hbvmentioning
confidence: 83%
“…The distinct roles of M1 and M2 macrophages involved in HBV infection raise the possibility that HBV may promote M2 polarization of macrophages to impair the Type 1 T helper cell immune response, resulting in persistent infection and disease progression. A most recent study 87 supported the hypothesis that HBV suppresses M1 macrophage cytokine (IL-6 and IL-1b) expression and promotes M2 macrophage cytokine (IL-10) expression to favor HBV infection. Although the precise mechanism remains unclear, several in vitro studies have revealed that either hepatitis B surface antigen or hepatitis B e antigen may make a contribution.…”
Section: Effect Of Hbv On Macrophage Phenotypementioning
confidence: 89%